Analisis Faktor-faktor yang Mempengaruhi Permintaan Kopi Indonesia - Aristy, Yogi; Muhamad Emil Rachman (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
In Indonesia, coffee is one of the primary goods in the plantation sub-sector which plays a large role. Coffee farmers and other economic actors involved in processing and marketing use this function as a source of income, employment and foreign exchange. This study aims to study the factors that influence the demand for Indonesian coffee in Indonesia. The data analyzed is time series data for 2010-2020, the analysis tool uses multiple linear regression models estimated using the Ordinary Least Square (OLS) method using SPSS 25. Based on the results of data analysis, the factors influencing demand for Indonesian coffee. The researcher concludes that the price of Indonesian coffee, the price of Indonesian tea and Indonesia's GDP can well explain the equation for Indonesian coffee demand, but individually only the price of Indonesian tea and Indonesia's GDP have a significant effect on explaining the equation for Indonesian coffee demand.